1984
DOI: 10.1093/brain/107.2.619
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Gaze Palsies in Monkeys and Their Relation to Uman Pathology

Abstract: Lesions were placed in the paramedian pontine reticular formation ( PPRF ) of monkeys and the resulting gaze palsies studied. Brainstem regions were identified by single cell recordings before kainic acid was injected to selectively destroy neuronal cell bodies in the vicinity. Unilateral PPRF lesions led to a loss of all rapid eye movements towards the ipsilateral side. Deficits were identical to those after experimental electrolytic lesions in monkeys, or structural lesions in humans. Bilateral PPRF lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
3

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(49 citation statements)
references
References 29 publications
(24 reference statements)
5
39
1
3
Order By: Relevance
“…There has been one report of extensive Purkinje cell loss affecting most of the cerebellar cortex, including the flocculus, in SCA6 patients (Gomez et al 1997). Our neuro-otological findings suggested lesions in the vermis, flocculus, paraflocculus or nodulus with sparing of the paramedian pontine reticular formation, and these findings were consistent with the purely cerebellar disorders of eye movements in previous reports (Zee et al 1981;Henn et al 1984;Fetter et al 1994;Moschner et al 1994;Buttner and Grundei 1995;Buttner et al 1998;Burk et al 1999;Lin and Young 1999). Further studies will be necessary to confirm the relationship between anatomical lesions and the neuro-otological features of SCA6, especially the relationship between DPN and lesions of the flocculus or nodulus.…”
Section: Neuro-otological Aspectsupporting
confidence: 92%
“…There has been one report of extensive Purkinje cell loss affecting most of the cerebellar cortex, including the flocculus, in SCA6 patients (Gomez et al 1997). Our neuro-otological findings suggested lesions in the vermis, flocculus, paraflocculus or nodulus with sparing of the paramedian pontine reticular formation, and these findings were consistent with the purely cerebellar disorders of eye movements in previous reports (Zee et al 1981;Henn et al 1984;Fetter et al 1994;Moschner et al 1994;Buttner and Grundei 1995;Buttner et al 1998;Burk et al 1999;Lin and Young 1999). Further studies will be necessary to confirm the relationship between anatomical lesions and the neuro-otological features of SCA6, especially the relationship between DPN and lesions of the flocculus or nodulus.…”
Section: Neuro-otological Aspectsupporting
confidence: 92%
“…That is, the saccadic eye movement is encoded by the temporal discharge of burst neurons [35]. Experimental or clinical lesions of the PPRF and riMLF abolish or slow saccades [7,11,12]. Most patients with PSP eventually show slow [24] or absent vertical saccades, and neuropathological studies have demonstrated involvement of the region in which riMLF lies [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Upward extension of the lesion can be responsible for horizontal gaze palsy, but some previous reports indicated that there was also vertical gaze palsy. 6 ' 8 An animal experimental study 9 suggested the relation of vertical saccade palsy to the lower pontine lesion. Bilateral damage of the caudal paramedian pontine reticular formations (PPRFs) ventral to the abducens nuclei leads to a severe disruption of vertical rapid eye movements in it.…”
Section: Discussionmentioning
confidence: 99%